THE PERCEPTION OF INDUSTRY ABOUT PRAKERIN’S STUDENT PERFORMANCE OF BUILDING DRAWING ENGINEERING COMPETENCE PROGRAM AT SMKN 2 PAYAKUMBUH ACADEMIC YEARS OF 2015/2016 - 1834-1847 , Sandi Junia Putra (Universitas Negeri Padang, 2016)
The purpose of this research to described the perception of industry in Payakumbuh City and Pekanbaru City about student’s performance of Building Drawing Engineering Competence Program (TGB) at SMKN 2 Payakumbuh, Academic Years of 2015/2016 have did Prakerin activity. The type of this research was descriptive research. The populations of this research were the companies coorperation with Competence Program TGB in Payakumbuh City and Pekanbaru City. The totally of companies were 9. Sample of this research were supervisors and trainers of Prakerin’s students in the companies which the totaly were 18 peoples. Sample collection method was total sampling. The variable of this research was only one variable. Data collection method was questionnaire. There were 42 items of the questionnaires. Before data collected, to did pre-test for supervisors and trainers Prakerin’s students of companies in Padang City which the totally were 30 peoples. This was to did it, to knew what were the instruments valid and reliable. Data analysis was manually and used Microsoft Excel 2007 software program. The result percentage perception of industry about student’s performance of Competence Program TGB at SMKN 2 Payakumbuh, Academic Years 2015/2016 have did Prakerin’s activity in Payakumbuh City was 63,38 % and 55,77 % in Pekanbaru City. The result of this research show that the percentage of two industries perception were still not good.Keyword: Perception, Industry, Prakerin